UNUSUAL RESPONSES OF GUIANA DOLPHINS (SOTALIA GUIANENSIS) TO THE PRESENCE OF SWIMMERS AND BOATS: Respostas incomuns de botos-cinza (Sotalia guianensis) à presença de nadadores e embarcações - Moreira de Gurjão, Livio; Leite de Oliveira, Cinthya; Lima do Nascimento, Heideger; Luz Carvalho, Vitor; Oliveira de Meirelles, Ana Carolina (Arquivos de Ciências do Mar, 2024)
The Guiana dolphin, Sotalia guianensis, classified as 'Vulnerable' to extinction in Brazil, exhibits a particularly small population within Mucuripe embayment, Ceará state, Northeastern Brazil. This study investigated their behavioral responses from October 2019 to May 2021 as part of the environmental licensing requirements for dredging and land reclamation activities. Thirty-two boat surveys were conducted, with dolphins observed in 97% of them. Two 'unusual' responses to the presence of boats and swimmers were noted: a neutral reaction, when a group of five dolphins continued foraging despite nearby swimmers; and a positive response, when three dolphins deliberately approached the research boat, engaging in spy-hopping and sideways swimming, suggesting curiosity towards our presence. These unusual reactions highlight concerns regarding potential human-dolphin interactions in Mucuripe embayment, underscoring the need for continuous systematic monitoring. Such efforts are crucial to provide the appropriate subsidies aimed at preserving natural dolphin behaviors. Keywords: Cetaceans, marine mammals, endangered species, behavior, interactions, Mucuripe embayment.